KEPRAKTISAN ENSIKLOPEDIA FAMILI MYRTACEAE KOLEKSI KEBUN RAYA BANUA UNTUK MELATIHKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA - Rabiatul Adawiyah; Muhammad Zaini; Kaspul Kaspul (Bio-Lectura : Jurnal Pendidikan Biologi, 2023)
Developments in the 21st century in the field of education seek students to be able to think critically and be aware of environmental conditions. Phrases Think global, act local are sentences related to awareness of environmental conditions. The real form of the phrase think globally (think globally) is to develop a product in the form of an encyclopedia that contains information about biology, while the real form of the phrase act locally (act locally) is in the form of research conducted. The encyclopedia is a comprehensive collection of information on the morphology of the myrtaceae family in the collection of kebun raya banua. The purpose of this study is related to describing practicality. Development research model to improve and enhance previous products. Research development using Tessmer's formative evaluation design. Individual test (one to one evaluation), and small group test (small group evaluation). The personality test subjects (one to one evaluation) were three students who had taken plant morphology courses related to content practicality data, the small group evaluation subjects were four students who had taken plant morphology courses related to practical expectations data. The results of the development research show a practical encyclopedia